(untitled) (Journal of Social Sciences Review, 2025)
This research examines the scholastic and cultural transitions of Pakistani students in China before and after the COVID-19 break. The study focuses on exploring how the pandemic affected the academic daily schedule, interaction with peers and community, and accessing cultural resources as well as the possibilities of the students’ resistance and creativity. Based on a survey and interviews conducted with Pakistani students studying in Chinese universities, this study examines the problems like; instructional challenges of online learning, stress, and; limited social contact due to the COVID-19 outbreak. It also puts emphasis on how students cope with these challenges such as the use of Information communication technologies in learning and networking. After the pandemic, the research contributes to understanding in-person academically related interactions and cultural transition focusing on institutional support arrangements. The results enrich the theoretical knowledge about the patterns of international student mobility, cross-cultural adjustment, and the long-term effects of global emergencies on education. The findings in this study can be of valuable support to policymakers and universities to improve the lives of international students in the post-COVID-19 era.